Intramedullary telescopic nailing method applied in cases with osteogenesis imperfecta and our results - Ozer, Ilyas; Demir, Sukru; Yilmaz, Mehmet (Bmc, 2025)
Osteogenesis Imperfecta (OI) is a connective tissue disease that is the most common genetic cause of osteoporosis and is characterized by deformities and fractures in long bones. This disease occurs due to the deficiency of Type 1 collagen. Orthopedically, it is aimed to treat and prevent deformities and fractures in the extremities. The aim of this study is to evaluate the results of patients who were hospitalized with the diagnosis of osteogenesis imperfecta in our clinic and who underwent telescopic nailing by comparing them with the literature.In this study, 15 patients diagnosed with Osteogenesis Imperfecta who were admitted to the Orthopedics and Traumatology Clinic of F & imath;rat University Faculty of Medicine Hospital and treated surgically between 2015 and 2021 were retrospectively examined. A total of 43 lower extremity bones were treated with telescopic nails, and the patients were followed for an average of 4 years. The primary outcome was the rate of revision surgeries required due to complications such as refracture, pseudoarthrosis, or nail migration. Descriptive statistical analysis was performed using SPSS software (version 27.0).Total of 43 lower extremity bones were surgically treated with telescopic nails. The patients were followed for an average of 4 years. The mean revision time was 28 months for femur and 35 months for tibia. The revision rate was 16.6% for femoral surgery and 7.69% for tibial surgery. No cases of non-union or postoperative infection were observed. The overall complication rate was 13.9%. The average union time was 45 days. No postoperative infections were observed in any of the 43 operated extremities. Intraoperative bleeding was generally minimal and well-controlled; only 4 patients required perioperative transfusion of one unit of erythrocyte suspension. According to Hoffer and Bullock ambulation grading, 11 patients had unassisted ambulation, while only 2 remained wheelchair-dependent.These results suggest that the telescopic nail method, when applied with a minimally invasive approach, may be considered a reliable technique with a low complication rate and favorable functional outcomes in the management of OI-related lower extremity deformities.
Keywords: Osteogenesis imperfecta; Telescopic nail method; Shish kebab osteotomy; Fracture; Deformity